2013
DOI: 10.1002/cmmi.1532
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the biodistribution of an [18F]FDG‐loaded perfluorocarbon double emulsion using dynamic micro‐PET in rats

Abstract: Perfluorocarbon (PFC) double emulsions loaded with a water-soluble, therapeutic agent can be triggered by ultrasound in a process known as acoustic droplet vaporization (ADV). Elucidating the stability and biodistribution of these sonosensitive vehicles and encapsulated agents are critical in developing targeted drug delivery strategies using ultrasound. [18F]fluorodeoxyglucose (FDG) was encapsulated in a PFC double emulsion and the in vitro diffusion of FDG was assessed using a Franz diffusion cell. Using dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…PET is an attractive nuclear imaging technique based on the detection of photons arising from annihilation of electron (e − ) with a positron (e + ), emitted by PET radionuclide. PET can image deep tissue with high sensitivity (0.02–0.1 cps/Bq) and is widely used in preclinical and clinical imaging of diseases . PET offers non‐invasive quantification of biodistribution and concentration of probes labeled with radionuclides in a body and bloodstream such as determination of drug concentration in tissues as low as 10 −12 mol L −1 .…”
Section: Pharmacological Nanoparticles From Emulsion Techniquesmentioning
confidence: 99%
“…PET is an attractive nuclear imaging technique based on the detection of photons arising from annihilation of electron (e − ) with a positron (e + ), emitted by PET radionuclide. PET can image deep tissue with high sensitivity (0.02–0.1 cps/Bq) and is widely used in preclinical and clinical imaging of diseases . PET offers non‐invasive quantification of biodistribution and concentration of probes labeled with radionuclides in a body and bloodstream such as determination of drug concentration in tissues as low as 10 −12 mol L −1 .…”
Section: Pharmacological Nanoparticles From Emulsion Techniquesmentioning
confidence: 99%
“…In a highly perfused organ such as liver, with an average fractional blood volume of 31% (Schwickert et al, 2005), 3.23 Â 10 5 droplets/mL of blood are required for HIFU lesions in a 70 kg human with 5 L blood volume. Systemically, this yields 2.3 Â 10 7 droplets/kg, which is 282-times lower in concentration than a recent biodistribution study where a similar emulsion was safely tolerated at 6.5 Â 10 9 droplets/kg (Fabiilli et al, 2013).…”
Section: B Lesion Formation Results Using a Clinical Hifu Systemmentioning
confidence: 88%
“…However, UCAs also move the greatest heating position from the focus by up to 2 cm for a given transducer geometry and aberrating tissues intervening the acoustic path as well as create surface lesions for concentrations greater than 0.1% (v/v), with some damage well outside the lesion (Tung et al, 2006). Alternatively, acoustic droplet vaporization (ADV) is an ultrasound-based method of converting biocompatible microdroplets (Fabiilli et al, 2013) into microbubbles. When exposed to acoustic pressures above the vaporization threshold, injected perfluorocarbon microdroplets-which are similar in size to UCAs-produce microbubbles that are more than 100-fold larger in volume than the original microdroplets, resulting in a local increase in the acoustic absorption.…”
Section: Introductionmentioning
confidence: 98%
“…This strategy was also used by Fabiilli and co-workers to carry and release chlorambucil, a lipophilic chemotherapeutic [20], and thrombin, a serine protease used in the treatment of pseudoan-eurysms [21]. More recently, Fabiilli et al also reported the biodistribution of such composite droplets of perfluorocarbon (6 µm or less in diameter) in rats [22]. While this technology appeared very useful for internal tattooing of tissues, the slow leakage of the encapsulated compound observed from uninduced droplets appeared as a potential drawback to envision the adaptation of this concept to the delivery of highly toxic anticancer agents.…”
Section: Introductionmentioning
confidence: 98%